Advances in accounting behavioral research. - Karim, Khondkar E., 1961- (Emerald Publishing Limited, 2017)
Advances in Accounting Behavioral Research publishes high-quality research encompassing all areas of accounting, including financial, auditing, taxation, managerial, and information systems, addressing a broad range of issues that affect the users, preparers, and assurers of accounting information. Further, this research incorporates theory from, and contributes knowledge and understanding to, applied psychology, sociology, management science, and behavioral economics.